ANALISIS TEBAL PERKERASAN RUNWAY PADA BANDARA INTERNASIONAL OE-CUSSE, TIMOR LESTE - Sahat Martua Sihombing; Achmad Pahrul Rodji; Al Muzamil (Fakultas Teknik Universitas Krisnadwipayana, 2022)
Oecusse-Ambeno is one of the districts in Timor Leste which is being developed by the government. Oneof the developments is through the implementation of an airport project called the